All the money in the world eaudiobook What the happiest people know about getting and spending. - Vanderkam, Laura (Ascent Audio, 2012)
How happy would you be if you had all the money in the world? The universal lament about money is that there is never enough. We spend endless hours obsessing over our budgets and investments, trying to figure out ways to stretch every dollar. We try to follow the advice of money gurus and financial planners, then kick ourselves whenever we spend too much or save too little. For all of the stress and effort we put into every choice, why are most of us unhappy about our finances? According to Laura Vanderkam, the key is to change your perspective. Instead of looking at money as a scarce resource, consider it a tool that you can use creatively to build a better life for yourself and the people you care about. For instance, the average couple spends $5,000 on engagement and wedding rings, making these pricey purchases largely because everyone else does. But what if you decided to spend $300 on rings and apply the rest to future date nights, weekend getaways, and thinking-of-you bouquets over the next ten years? In he long run, what would bring more joy to your marriage? Likewise, will owning a home with a pristine lawn and a two-car garage—the American Dream—really make you more satisfied? Or are you saving up for this investment just because financial planners tell you it's worth it? Vanderkam shows how each of us can figure out better ways to use what we have to build the lives we want. Drawing on the latest happiness research as well as the stories of dozens of real people, Vanderkam offers a contrarian approach that forces us to examine our own beliefs, goals, and values. Among her advice: Laugh at the Joneses: It's human nature to compare yourself to those around you, but you can create lifestyle hat rings you personal satisfaction without copying your neighbors. Give yourself the best weekend ever: Studies show that experiences often bring more pleasure than material goods. With a little planning and creativity, you can give yourself a memorable getaway without leaving town or going broke. Embrace the selfish joy of giving: Giving back not only helps you build karma, it also helps you build a community—which is much more fulfilling than a tax deduction. All the Money in the World is a practical and inspiring guide that shows how money can buy happiness—if we spend it wisely.